Partial Characterization of Polysaccharides Isolated from Defatted Desiccated Coconut Kernel - Yalegama, Loku Liyana Waduge Chandi; Karunaratne, Desiree Nedra; Sivakanesan, Ramaiah (International Coconut Community, 2023)
Industrial processing of coconut oil generates considerable biomass of dehydrated defatted coconut kernel (DDCK) which is composed of food-grade fiber. The objective of this study was to separate and isolate polysaccharides and oligosaccharides in defatted coconut kernel, and to determine the partial structure using sugar profile. Coconut cell wall polysaccharides (CCWP) obtained from DDCK were used to sequentially extract pectin (with 5% ammonium oxalate-oxalic acid), HCI (with 4% NaOH), HCII (with 10% NaOH), HCIII (with 17.5% NaOH) and the remaining fraction as non-extractible matter referred as NaOH non-extractive. Results indicated that CCWP composed of 19% pectin, 29.6% HCI, 12% HCII, no detectable HCIII and NaOH non-extractive of 15%. The sugar profile of pectin, was 6.14% rhamnose, 3.31% arabinose, 61.72% mannose and 18.71% galactose. HCI composed of rhamnose 13.29%, arabinose 4.49%, xylose 22.84%, mannose 50.98%, galactose 5.9% and glucose 3.39%. HCII contained rhamnose 37.12%, arabinose 3.35%, Mannose 27.15% and galactose 5.76%, while NaOH non-extractive contained rhamnose 22.5%, mannose 23.95%, galactose 16.35% and glucose 37.05%. Partial hydrolysis followed by concentration with Sephadex G15 size exclusion chromatography was able to separate oligosaccharide having rhamnose 15.3%, mannose 52.5% and galactose 32.2% from pectin while xylose 0.6%, mannose 95.6%, galactose 1.1% and glucose 2.7% from HCII. Results indicated the presence of rhamnogalactomannan and xylogalactoglucomanan in coconut kernel.